Alteration in the Culex pipiens transcriptome reveals diverse mechanisms of the mosquito immune system implicated upon Rift Valley fever phlebovirus exposure. - Ana I Núñez; Anna Esteve-Codina; Jèssica Gómez-Garrido; Marco Brustolin; Sandra Talavera; Miguel Berdugo; Marc Dabad; Tyler Alioto; Albert Bensaid; Núria Busquets (Public Library of Science (PLoS), 2020)
Rift Valley fever phlebovirus (RVFV) causes an emerging zoonotic disease and is mainly transmitted by Culex and Aedes mosquitoes. While Aedes aegypti-dengue virus (DENV) is the most studied model, less is known about the genes involved in infection-responses in other mosquito-arboviruses pairing. The main objective was to investigate the molecular responses of Cx. pipiens to RVFV exposure focusing mainly on genes implicated in innate immune responses. Mosquitoes were fed with blood spiked with RVFV. The fully-engorged females were pooled at 3 different time points: 2 hours post-exposure (hpe), 3- and 14-days post-exposure (dpe). Pools of mosquitoes fed with non-infected blood were also collected for comparisons. Total RNA from each mosquito pool was subjected to RNA-seq analysis and a de novo transcriptome was constructed. A total of 451 differentially expressed genes (DEG) were identified. Most of the transcriptomic alterations were found at an early infection stage after RVFV exposure. Forty-eight DEG related to immune infection-response were characterized. Most of them were related with the RNAi system, Toll and IMD pathways, ubiquitination pathway and apoptosis. Our findings provide for the first time a comprehensive view on Cx. pipiens-RVFV interactions at the molecular level. The early depletion of RNAi pathway genes at the onset of the RVFV infection would allow viral replication in mosquitoes. While genes from the Toll and IMD immune pathways were altered in response to RVFV none of the DEG were related to the JAK/STAT pathway. The fact that most of the DEG involved in the Ubiquitin-proteasome pathway (UPP) or apoptosis were found at an early stage of infection would suggest that apoptosis plays a regulatory role in infected Cx. pipiens midguts. This study provides a number of target genes that could be used to identify new molecular targets for vector control.